Analysis of healthcare professionals’ perceptions towards individuals with disabilities: Influence of sociodemographic and professional determinants - Amal Chairi-Achari; Kenza Chaoui; Akram Touil; Amina Barkat; Majdouline Obtel (Advances in Medicine, Psychology, and Public Health)
Introduction: Healthcare professionals’ understanding of individuals with disabilities is essential to delivering equitable, high-quality care and fostering social inclusion. This study explores healthcare professionals' perceptions of persons with disabilities (PWDs) in Rabat, Morocco, analyzing the influence of sociodemographic and professional factors and identifying key determinants shaping these perceptions. Methods: An analytical cross-sectional study was conducted between October and December 2021. Questionnaires were distributed to 206 healthcare professionals, and responses from 92 participants were analyzed using bivariate and multivariate statistical methods. Results: Of the respondents, 26% held negative perceptions of PWDs, while 74% reported positive perceptions. Significant associations were identified between perceptions and factors such as gender, knowledge of disability management methods, and systematic screening practices. Multivariate analysis highlighted that knowledge of disability management methods and systematic screening significantly increased the likelihood of positive perceptions. Discussion: This study underscores the need to address knowledge and training gaps among healthcare professionals, emphasizing the importance of fostering empathy and inclusivity. By identifying key determinants, the findings offer actionable insights to improve professional practices and advance inclusive healthcare for individuals with disabilities.